Evaluation of the Effectiveness of PWM and MPPT Controllers in Improving the Performance of Off-Grid Solar Power Plants in NFT Hydroponic Systems - Wibowo, Tegar Satrio; Kusban, Muhammad (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The decreasing availability of agricultural land and the growing demand for sustainable food production have encouraged the adoption of hydroponic cultivation systems supported by renewable energy sources. In off-grid Nutrient Film Technique (NFT) hydroponic systems, the reliability of electrical power—particularly for continuous pump operation—is critical for plant growth. Methodology: A quantitative experimental approach was employed using a 50 Wp solar panel, a 12 V 10 Ah battery, and a 12 W DC water pump operating under identical system configurations. Electrical parameters, including charging voltage, current, and power, were measured during daylight hours, while nighttime pump operating duration was used as a functional performance indicator. Main Findings: The results demonstrate that the MPPT controller consistently produced higher and more stable charging power (up to 13.05 W) compared to the PWM controller (approximately 12 W). This improved charging performance translated into longer nighttime pump operation, with MPPT sustaining operation for up to 11 hours 40 minutes, whereas PWM supported only 9 hours 30 minutes to 10 hours 15 minutes. The findings confirm that MPPT controllers are more effective in optimizing solar energy utilization and enhancing battery endurance in real-world hydroponic applications. Novelty/Originality of this study: The novelty of this study lies in its integration of electrical performance analysis with practical operational outcomes, offering applied insights for the design of reliable and sustainable solar-powered hydroponic systems, particularly in regions with limited grid access.